Measurement of Mean Cardiac Dose for Various Breast Irradiation Techniques and Corresponding Risk of Major Cardiovascular Event - Merino Lara, Tomas Rodrigo; Fleury, Emmanuelle; Mashouf, Shahram; Helou, Joelle; McCann, Claire; Ruschin, Mark; Kim, Anthony; Makhani, Nadiya; Ravi, Ananth; Pignol, Jean-Philippe (Frontiers in Oncology, 2014)
After breast conserving surgery, early stage breast cancer patients are currently treated with a wide range of radiation techniques including whole breast irradiation (WBI), accelerated partial breast irradiation (APBI) using high dose rate (HDR) brachytherapy, or 3D conformal radiotherapy (3D-CRT). This study compares the mean heart’s doses for a left breast irradiated with different breast techniques. An anthropomorphic Rando phantom was modified with gelatin-based breast of different sizes and tumors located medially or laterally. The breasts were treated with WBI, 3D-CRT or HDR APBI. The heart’s mean doses were measured with Gafchromic films and controlled with optically stimulated luminescent dosimeters (OSLDs). Following the model reported by Darby (16), major cardiac were estimated assuming a linear risk increase with the mean dose to the heart of 7.4% per gray. Whole breast irradiation lead to the highest mean heart dose (2.99 Gy) compared to 3D-CRT APBI, (0.51 Gy), multicatheter (1.58 Gy) and balloon HDR (2.17 Gy) for a medially located tumor. This translated into long-term coronary event increases of 22%, 3.8%, 11.7%, and 16% respectively. The sensitivity analysis showed that the tumor location had almost no effect on the mean heart dose for 3D-CRT APBI and a minimal impact for HDR APBI. For WBI large breast size and set-up errors lead to sharp increases of the mean heart dose. Its value reached 10.79 Gy for women with large breast and a set-up error of 1.5 cm. Such a high value could increase the risk of having long-term coronary events by 80%. Comparison among different irradiation techniques demonstrates that 3D-CRT APBI appears the safest one with less probability of having cardiovascular events in the future. A sensitivity analysis showed that WBI is the most challenging technique for patients with large breasts or when significant set-up errors are anticipated. In those cases additional heart shielding techniques are required.